Correction: Chun et al. Synergistic Antiviral Activity of Xanthan Gum and Camostat Against Influenza Virus Infection. Viruses 2025, 17, 301 - Kyeunghwa Chun; Yujeong Na; Byeongyong Kim; Dongjin Lee; Jongseo Choi; Gwanyoung Kim; Sokho Kim; Min-Soo Kim (Viruses)
In the original publication [...]